2016
DOI: 10.1016/j.jgar.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into the emergence and spread of international clones of healthcare-, community- and livestock-associated meticillin-resistant Staphylococcus aureus : Blurring of the traditional definitions

Abstract: Please cite this article as: Bal AM, Coombs GW, Holden MTG, Lindsay JA, Nimmo GR, Tattevin P, Skov RL, Genomic insights into the emergence and spread of international clones of healthcare-, community-and livestock-associated meticillinresistant Staphylococcus aureus: blurring of the traditional definitions, Journal of Global Antimicrobial Resistance (2010), http://dx.doi.org/10.1016/j.jgar. 2016.04.004 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
113
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 72 publications
(53 reference statements)
1
113
0
3
Order By: Relevance
“…There have been several reports of MRSA colonization and/or infections in dairy cattle since the first report of MRSA in mastitis in 1972 (Devriese et al, 1972; Monecke et al, 2007; Fessler et al, 2010; Huber et al, 2010). LA-SA ST398 was originally reported to have emerged in the Netherlands among pigs and pig farmers in 2003 (Voss et al, 2005), and was later found in Austria, Germany, and Denmark (Van Cleef et al, 2011; Bal et al, 2016). It developed into an overwhelmingly dominant lineage in Europe and North America (Vanderhaeghen et al, 2010; Cuny et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports of MRSA colonization and/or infections in dairy cattle since the first report of MRSA in mastitis in 1972 (Devriese et al, 1972; Monecke et al, 2007; Fessler et al, 2010; Huber et al, 2010). LA-SA ST398 was originally reported to have emerged in the Netherlands among pigs and pig farmers in 2003 (Voss et al, 2005), and was later found in Austria, Germany, and Denmark (Van Cleef et al, 2011; Bal et al, 2016). It developed into an overwhelmingly dominant lineage in Europe and North America (Vanderhaeghen et al, 2010; Cuny et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…LA-MRSA was irst detected in milk with bovine mastitis from Belgium in 1972 [11][12][13]. Thereafter, MRSA reports in various food and companion animals, such as pigs, catle, chickens, dogs, cats, and horses, have increased [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…n recent decades, the overall incidence of methicillin-resistant Staphylococcus aureus (MRSA) infections has greatly increased due to the emergence of community-associated MRSA (CA-MRSA), which are increasingly displacing hospitalassociated-MRSA (HA-MRSA) strains in health care settings (1). Methicillin resistance is mediated by the mecA-encoded low-affinity penicillin binding protein 2a carried on the mobile staphylococcal cassette chromosome mec element (SCCmec).…”
mentioning
confidence: 99%